Pengaruh Tunneling Incentive Dan Mekanisme Bonus Terhadap Tax Avoidance: Systematic Literature Review - Naely Choeri Akmali; Putri Dwi Rosalinda Prayoga; Dien Noviany Rahmatika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The importance of taxes in economic development for developing countries, with a focus on tax avoidance as the main obstacle in achieving optimal tax revenues. The aim of this research is to review the influence of bonus mechanisms and tunneling incentives on tax avoidance in companies. This research method uses the Systematic Literature Review (SLR) method to analyze journals and articles published between 2017 and 2024, with a focus on the themes of tax, tunneling incentives, bonus mechanisms and tax avoidance. Of the 59 articles that have been selected, only 57 articles are used as research sources in this journal. The development of the number of publications related to the influence of bonus and tunneling incentive mechanisms on Tax Avoidance is still fluctuating from 2017 - 2024. It can be concluded that bonus mechanisms and tunneling incentives have different roles in influencing tax avoidance. various research sources: incentive tunneling variables can reduce tax avoidance, while bonus mechanism variables can increase tax avoidance. Tax evasion is a complex problem that requires clear consideration and law enforcement by the government and business world to ensure legal and fair tax payment practices.